Synthesis and Properties of Polyurethane Elastomers from a Phosphorus-Containing Chain Extender - Chen, Zhengyan; Li, Zhen; Liu, Jin (Asian Journal of Chemistry, 2012)
A series of phosphorus-containing polyurethane elastomers (P-PU) were prepared, which are based on synthesized bis(3-hydroxy phenyl)phenyl phosphate (BPP) as chain extender and phosphorus resource reacting with NCO-terminated polyurethane prepolymers from 4,4'- diphenylmethane diisocyanate (MDI) reacting with different soft segments of polyether polyols, polytetrahydrofuran ether glycol, polyester polyols, respectively. The bis(3-hydroxy phenyl)phenyl phosphate and phosphorus containing polyurethane elastomers structures were confirmed by FTIR spectroscopy. The properties of polyurethane elastomers of hydrophilicity, thermo-stability and mechanical property were analyzed. The results showed that the hydrophilicity of phosphorus containing polyurethane elastomers was enhanced with the increased amount of phosphorus containing; the soft segments content and types definitely influence the phosphorus containing polyurethane elastomers thermal stability.